Respostas

2013-09-24T15:41:44-03:00
A) 2x + 0y = 30             logo: 15 + y = 17  
   x = 30/2                                 y= 2
   x = 15

b) multiplicando a 1ª sentença por -3 temos:
  -9x -3y = -15
  x + 3y = -1

assim: -8x + 0y = -16
             x = 2

        x + 3y = -1
        2 + 3y = -1
        3y = -3
        y = -1

1 2 1
2013-09-24T15:42:37-03:00
A) 2x=30      15+y=17
x=30/2          y=2
x=15

b)  3x+y=5 (-3)
      x+3y= -1
-9x-3y=-15
x+3y= -1

-8x=-16 (-1)      x+3y=-1
8x=16             2+3y=-1
x=2               3y=-3
                     y=-1